2016
DOI: 10.1039/c6cc05326b
|View full text |Cite
|
Sign up to set email alerts
|

A planar triangular Dy3 + Dy3 single-molecule magnet with a toroidal magnetic moment

Abstract: A unique Dy6 complex with a planar Dy3 + Dy3 structure was assembled by delicately modifying the axial ligands. Single-molecule magnet behavior and meanwhile a toroidal magnetic moment in the ground state have been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…We have been involved in the design and utilization of various types of ligand families for the preparation of 3d/4f, and 4f,,, complexes. From our experience,, and those of others we have observed that flexible ligands that have multiple options to bind to a metal ion are often suitable to generate polynuclear complexes. Among the ligands that we have investigated, aroyl hydrazone ligands have been found to possess the following beneficial features.…”
Section: Resultsmentioning
confidence: 62%
“…We have been involved in the design and utilization of various types of ligand families for the preparation of 3d/4f, and 4f,,, complexes. From our experience,, and those of others we have observed that flexible ligands that have multiple options to bind to a metal ion are often suitable to generate polynuclear complexes. Among the ligands that we have investigated, aroyl hydrazone ligands have been found to possess the following beneficial features.…”
Section: Resultsmentioning
confidence: 62%
“…As P QTM 2 is smaller than P QTM , QTM is effectively suppressed in coupled dimers of SMMs . In the case of 4f SMMs, with a few exceptions, through‐space magnetic dipole–dipole (MD) interactions have a significant effect on the SMM behavior . When the magnetic easy axes of the magnetic dipoles are on the same straight line, only an axial component of the MD interactions exists, which scarcely affects P QTM , making P QTM 2 small.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In the case of 4f SMMs, with af ew exceptions, [10][11][12][13] through-space magnetic dipole-dipole (MD) interactions have as ignificant effect on the SMM behavior. [14][15][16][17][18][19][20][21][22][23][24][25] When the magnetic easy axes of the magnetic dipoles are on the same straight line, only an axial component of the MD interactions exists, which scarcely affects P QTM ,m aking P QTM 2 small. On the other hand, in the presence of transversal MD interactions, P QTM becomes larger,a nd hence, the magnetic relaxations are faster due to the larger off-diagonal matrix elements of the coupled ground states.…”
Section: Introductionmentioning
confidence: 99%
“…A static toroidal moment exists in various materials both microscopically and macroscopically, covering transition metal ions [68], biological and chemical macromolecules [69][70][71][72][73][74], bulk crystals [75][76][77][78][79][80], and glasses [81]. In macroscopic condensed matter, formation of toroidal moments in materials plays a vital role in the asymmetric ME.…”
Section: Toroidization and Me In Materialsmentioning
confidence: 99%